Photoassisted Construction of Holey Defective g‐C3N4 Photocatalysts for Efficient Visible‐Light‐Driven H2O2 Production - Shi, Li; Yang, Liuqing; Zhou, Wei; Liu, Yanyu; Yin, Lisha; Hai, Xiao; Song, Hui; Ye, Jinhua (Small (Weinheim an der Bergstrasse, Germany), 2018)
Holey defective g‐C3N4 photocatalysts, which are easily prepared via a novel photoassisted heating process, are reported. The photoassisted treatment not only helps to create abundant holes, endowing g‐C3N4 with more exposed catalytic active sites and crossplane diffusion channels to shorten the diffusion distance of both reactants from the surface to bulk and charge carriers from the bulk to surface, but also introduces nitrogen vacancies in the tri‐s‐triazine repeating units of g‐C3N4, inducing the narrowing of intrinsic bandgap and the formation of defect states within bandgap to extend the visible‐light absorption range and suppress the radiative electron–hole recombination. As a result, the holey defective g‐C3N4 photocatalysts show much higher photocatalytic activity for H2O2 production with optimized enhancement up to ten times higher than pristine bulk g‐C3N4. The newly developed synthetic strategy adopted here enables the sufficient utilization of solar energy and shows rather promising for the modification of other materials for efficient energy‐related applications. A holey defective g‐C3N4 photocatalyst can be prepared through a novel photo‐assisted heating process, and it shows much higher photocatalytic activity for H2O2 production with optimized enhancement up to 10 times higher than pristine bulk g‐C3N4, which is due to the introduction of abundant holes and nitrogen vacancies.